Air Pollution, housing and respirfatory tract Infections in Children: NatIonal birth Cohort study (PICNIC): study protocol. Issue 5 (3rd May 2021) - Favarato, Graziella; Clemens, Tom; Cunningham, Steven; Dibben, Chris; Macfarlane, Alison; Milojevic, Ai; Taylor, Jonathon; Wijlaars, Linda Petronella Martina Maria; Wood, Rachael; Hardelid, Pia
Abstract : Introduction: Respiratory tract infections (RTIs) are the most common reason for hospital admission among children <5 years in the UK. The relative contribution of ambient air pollution exposure and adverse housing conditions to RTI admissions in young children is unclear and has not been assessed in a UK context. Methods and analysis: The aim of the PICNIC study (Air Pollution, housing and respiratory tract Infections in Children: NatIonal birth Cohort Study) is to quantify the extent to which in-utero, infant and childhood exposures to ambient air pollution and adverse housing conditions are associated with risk of RTI admissions in children <5 years old. We will use national administrative data birth cohorts, including data from all children born in England in 2005–2014 and in Scotland in 1997–2020, created via linkage between civil registration, maternity and hospital admission data sets. We will further enhance these cohorts via linkage to census data on housing conditions and socioeconomic position and small area-level data on ambient air pollution and building characteristics. We will use time-to-event analyses to examine the association between air pollution, housing characteristics and the risk of RTI admissions in children, calculate population attributable fractions for ambient air pollution and housing characteristics, and use causal mediation analyses to explore the mechanisms through which housing and air pollution influence the risk of infant RTI admission. Ethics, expected impact and dissemination: To date, we have obtained approval from six ethics and information governance committees in England and two in Scotland. Our results will inform parents, national and local governments, the National Health Service and voluntary sector organisations of the relative contribution of adverse housing conditions and air pollution to RTI admissions in young children. We will publish our results in open-access journals and present our results to the public via parent groups and social media and on the PICNIC website. Code and metadata will be published on GitHub.